On horseshoe street : more tales from the provinces - Devendra, Tissa (Colombo : Vijitha Yapa Publications, 2005)
Memoirs of the author, government field officer, in differant provinces of Sri Lanka
Keywords: Devendra, Tissa; Sri Lanka -- Officials and employees -- Biography